2016
DOI: 10.1590/1678-457x.00415
|View full text |Cite
|
Sign up to set email alerts
|

The impact of convective drying on the color, phenolic content and antioxidant capacity of noni (Morinda citrifolia L.)

Abstract: The effect of thin-layer drying temperature on color, phenolic content and antioxidant capacity of noni slices was investigated. Noni slices were air-dried at 50, 60 and 70 °C under natural convection conditions. Drying curves were fitted to thin-layer drying models in order to evaluate the drying characteristics of the product. In addition, an unsteady-state diffusion equation was numerically solved considering both product shrinkage and a variable mass Biot number in boundary condition to accurately estimate… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
8
0
1

Year Published

2018
2018
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(9 citation statements)
references
References 32 publications
0
8
0
1
Order By: Relevance
“…It may lead to increased bioavailability [15]. Ana et al [14] demonstrated that convective drying caused a degradation of total phenolic (20-28%), the antioxidant capacity (82-93% DPPH inhibition) of dried noni.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…It may lead to increased bioavailability [15]. Ana et al [14] demonstrated that convective drying caused a degradation of total phenolic (20-28%), the antioxidant capacity (82-93% DPPH inhibition) of dried noni.…”
Section: Resultsmentioning
confidence: 99%
“…It's totally depended on the severity of drying and roasting conditions [13]. The effect of thin-layer drying temperature on color, phenolic content and antioxidant capacity of noni slices was investigated [14]. Thermal degradation of flavonol glycosides in noni leaves during roasting was investigated [15].…”
Section: Introductionmentioning
confidence: 99%
“…All the infrared dried bee pollen samples showed lower L* and b* values than the fresh bee pollen while a* values of the infrared dried bee pollen samples were slightly higher than that of the fresh bee pollen, but the difference was not statistically significant (P > 0.05). The increase in a* value and decrease in L* value could result from non-enzymatic browning (Maillard reaction) during the drying process (Mireles-Arriaga et al 2016;Doymaz 2018). The parameter L* indicates the darkness or lightness of the colour, and L* value decreased from 52.72 to 41.95 when the infrared power was increased from 50 W to 88 W, respectively.…”
Section: Resultsmentioning
confidence: 99%
“…The results of the FRAP assay were in agreement with the outcome of the DPPH experiments, in which the MIs extract had the highest antioxidant activity followed by that of the MCf extract. Research reported by Mireles-Arriaga et al (2016) suggested that the phytochemical screening of the crude aqueous fruit extract of noni (M. citrifolia) possessed a total phenolic content of 22.76 mg GAE/g, which was similar to the results obtained for the total phenolic content of the curd fortified with the crude aqueous fruit extract of noni (16.869 ± 0.581 mg GAE/g), suggesting the high capability of fortified curd to retain the antioxidant content even though the liquid whey was discarded from the semi-solid curd by centrifugation. The results obtained from both assays suggested that curds fortified with crude aqueous extracts of M. indica and M. citrifolia were appreciated for their good milk-coagulating abilities as well as for being a source of antioxidants.…”
Section: Discussionmentioning
confidence: 98%